An Assessment of Medication Errors Among Pediatric Patients in Three Hospitals in Freetown Sierra Leone: Findings and Implications for a Low-Income Country - Abiri OT; Ninka A; Coker J; Thomas F; Smalle IO; Lakoh S; Turay FU; Komeh J; Sesay M; Kanu JS; Mustapha AM; Bell NVT; et al. (Dove Medical Press, 2024)
Onome T Abiri,1,2 Alex Ninka,3 Joshua Coker,4 Fawzi Thomas,2,5 Isaac O Smalle,6 Sulaiman Lakoh,4 Foday Umaro Turay,7 James Komeh,2,3 Mohamed Sesay,2,7 Joseph Sam Kanu,8 Ayeshatu M Mustapha,9 Nellie VT Bell,9 Thomas Ansumus Conteh,2,5 Sarah Kadijatu Conteh,10 Alhaji Alusine Jalloh,10 James BW Russell,4 Noah Sesay,3 Mohamed Bawoh,1 Mohamed Samai,1 Michael Lahai7 1Department of Pharmacology and Therapeutics, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 2Department of Pharmacovigilance and Clinical Trials, Pharmacy Board of Sierra Leone, Freetown, Sierra Leone; 3Department of Clinical Pharmacy and Therapeutics, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 4Department of Internal Medicine, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 5Department of Pharmaceutics, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 6Department of Surgery, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 7Department of Pharmaceutical Chemistry, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 8Department of Community Medicine, College of Medicine and Allied Health Sciences, University of Sierra Leone, Freetown, Sierra Leone; 9Department of Pediatrics, Ola During Children Hospital, Freetown, Sierra Leone; 10Department of Pediatrics, King Harman Road Maternity and Children Hospital, Freetown, Sierra LeoneCorrespondence: Onome T Abiri, Department of Pharmacology and Therapeutics, College of Medicine and Allied Health Sciences, University of Sierra Leone Freetown, Sierra Leone/Department of Pharmacovigilance and Clinical Trials, Pharmacy Board of Sierra Leone, Freetown, Sierra Leone, Tel +23276370315, Email berylonome@gmail.comBackground: Pediatric patients are prone to medicine-related problems like medication errors (MEs), which can potentially cause harm. Yet, this has not been studied in this population in Sierra Leone. Therefore, this study investigated the prevalence and nature of MEs, including potential drug-drug interactions (pDDIs), in pediatric patients.Methods: The study was conducted in three hospitals among pediatric patients in Freetown and consisted of two phases. Phase one was a cross-sectional retrospective review of prescriptions for completeness and accuracy based on the global accuracy score against standard prescription writing guidelines. Phase two was a point prevalence inpatient chart review of MEs categorized into prescription, administration, and dispensing errors and pDDIs. Data was analyzed using frequency, percentages, median, and interquartile range. Kruskal-Wallis H and Mann-Whitney U-tests were used to compare the prescription accuracy between the hospitals, with p< 0.05 considered statistically significant.Results: Three hundred and sixty-six (366) pediatric prescriptions and 132 inpatient charts were reviewed in phases one and two of the study, respectively. In phase one, while no prescription attained the global accuracy score (GAS) gold standard of 100%, 106 (29.0%) achieved the 80- 100% mark. The patient 63 (17.2%), treatment 228 (62.3%), and prescriber 33 (9.0%) identifiers achieved an overall GAS range of 80- 100%. Although the total GAS was not statistically significant (p=0.065), the date (p=0.041), patient (p=< 0.001), treatment (p=0.022), and prescriber (p=< 0.001) identifiers were statistically significant across the different hospitals. For phase two, the prevalence of MEs was 74 (56.1%), while that of pDDIs was 54 (40.9%). There was a statistically positive correlation between the occurrence of pDDI and number of medicines prescribed (r=0.211, P=0.015).Conclusion: A Low GAS indicates poor compliance with prescription writing guidelines and high prescription errors. Medication errors were observed at each phase of the medication use cycle, while clinically significant pDDIs were also reported. Thus, there is a need for training on prescription writing guidelines and medication errors.Keywords: pediatrics, prescription, medication errors, drug-drug interactions, Sierra Leone